Enhancing English Speaking Skill Through Action Learning Strategy for Ninth Grade Students of Smp N 6 Semarang - Hikmah, Ziyadatul (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This study describes the implementation of an action learning strategy in teaching speaking to ninth-grade students of SMP N 6 Semarang. It applies Classroom Action Research (CAR). The research subject was 34 students of IX H in the academic year of 2023/2024. This research was conducted in two cycles consisting of planning, acting, observing, and reflecting. Data were collected through observation and tests. The finding shows that the application of action learning strategies helps the students to enhance their speaking skills. This was identified by the result of the average score of the second cycle was 86.82 This showed that the score was improved than the first cycle. Based on data obtained from the results of classroom action research, there was an increase of average score 9.74% in cycle 1 and 11.58% in cycle 2. This indicated that students’ speaking ability was improved during teaching and learning process in the English classroom. The students were also more active, participative, and enthusiastic following the English lesson.